PENGARUH PENAMBAHAN EKSTRAK RUMPUT LAUT COKLAT TERHADAP KUALITAS ES KRIM - Fitri, Ilsa; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was based on the utilization of brown seaweed in food processingdoes not yet exist. Brown seaweed contains a high enough nutrient that is usefulfor thickening and stabilizer. This study aims to analyze the effect of the additionof chocolate seaweed extract as much as 5%; 10% and 15% of the quality of icecream in terms of color, smell, texture and flavor. The type of this study was pureexperiments using a complete randomized design method of one factor, namelythe addition of brown seaweed extract (0%, 5%, 10% and 15%) for threerepetitions. Types of data used are primary data sourced from 30 semi-trainedpanelists who provide answers to the questionnaire (organoleptic test format). Thedata that has been obtained is tabulated and analyzed by variant (ANAVA). Ifdifferent then proceed with Duncan's advanced test. The result of the researchshows that there is significant influence between 0%; 5%; 10% and 15% to thequality of chocolate seaweed ice. It can be concluded that the best percentage isfound in the addition of brown seaweed extract as much as 15% to the quality ofcolor, smell, texture and flavor.Keywords: Seaweed Extract Chocolate, Ice Cream, Quality.